(untitled) (Research, Society and Development, 2021)
Objective: To identify studies related to occurrences of cancer that have joint manifestations as the main symptom. Methodology: This is an integrative literature review, developed through the analysis of articles related to the topic, in which the bibliographic survey was carried out using the Scientific Electronic Library Online, Latin American and Caribbean Literature in Health Sciences database. and Google Scholar. Thus, the Controlled Descriptors in Health Sciences “articular manifestations” and neoplasia were used. Results: After conducting the research, 210 articles were identified and eight publications were elected after applying the inclusion and exclusion criteria and careful reading of the articles. In addition, they were categorized showing whether there was a strong relationship between the neoplasm and joint manifestations, until the categorization in which there was no relationship. Conclusion: There is a relationship between neoplasms and joint manifestations, as well as, it was identified that some types of cancer manifest through joint diseases since, in patients with lymphoma, gout, tissue reaction can be consequential and secondary. adjacent to lymphoma or synovial infiltration by lymphoma.